soil and crop management for organic carbon sequestration in a coconut based cropping system - Sudha B (Department of Agronomy, College of Agriculture, 2007)
Soil, the soul of infinite life, despite being the most basic of all natural resources is severely neglected these days. Quality of soil is determined much by the soil organic matter (SOM) content and hence SOM is regarded as the foundation of sustainable agriculture. The lesser addition of carbonaceous organic inputs to soil coupled with oxidative losses associated with tillage are the major reasons for the loss of SOM and hence organic carbon from cultivated soils. The oxidative losses of SOM contributes to release of carbon dioxide, the major greenhouse gas and aggravate the phenomenon of global warming. On the other hand, maintaining adequate carbon levels in soil by means of enriching SOM is important as carbon supports soil microbes by providing energy for their activities. Carbon sequestration is a management strategy which serves the twin purposes of storage of carbon in soil sinks preventing it’s loss as carbon dioxide into the atmosphere. Based on this,the present study was planned with the objective of developing a suitable soil and crop management practice for improving the soil organic carbon content through carbon sequestration in a coconut based cropping system. The study intended to evaluate the effect of the management practices on soil properties, crop growth and yield and to work out the economics of the system. The study was carried out in two experiments. Among the various management options to conserve and sequester carbon in agricultural soils cropping system approach, residue management and tillage holds much significance and were tried in Experiment I entitled “Influence of crops and cultivation practices on soil organic carbon enrichment and crop performance”. This experiment involved three coconut based cropping systems viz. coconut – banana (s1), coconut- maize (s2), and coconut- pineapple (s3). Management of residue was attempted as surface mulch (m1) and soil incorporation (m2) so as to assess their varying impact on carbon sequestration. Conventional tillage operations (t1) ensuring more soil aeration to enhance SOM decomposition was compared with reduced till method (t2). Altogether there were 12 + 1 (coconut alone as control) treatment combinations replicated thrice in factorial randomized block design. Perusal of the results indicated positive influence on most of the soil properties from the initial to the final stage of the experiment with treatments. Coconut- pineapple systems where pineapple residue was recycled, surface mulching of residues and reduced tillage contributed to significant build up of organic carbon and organic matter in the upper soil layer by the end of second year in comparison to other treatments. Significant increase in the enzymatic status of soil for soil enzymes dehydrogenase, phosphatase, urease, cellulase and protease noticed under these treatments is attributed to the maintanance of more SOM . These treatments also maintained higher humic acid status, available phosphorus, available potassium and cation exchange capacity at the final stage of the experiment. With surface mulching and reduced tillage, there was improvement in the aggregate stability of soil which resulted in favourable decrease of bulk density. Under surface mulching, coconut – pineapple and coconut – banana systems recorded higher water holding capacity. The fulvic acid content of soil was more with coconut – pineapple system and reduced tillage. The surface mulched plots maintained higher humic acid : fulvic acid ratios. The total and available nitrogen status of soil was found higher and comparable under coconut – banana and coconut – pineapple systems. With surface mulching and reduced tillage in coconut – banana systems, more number of suckers and higher biomass of banana resulted. For pineapple, these treatments effected in better plant height, plant spread, reduction in the number of days to flowering, increased fruit girth and fruit yield. For first and second crop of maize, higher grain yield resulted from surface mulching. The coconut yield was not significantly influenced by treatments at the end of the study. The Benefit : Cost ratio revealed that coconut – pineapple systems, surface mulching and reduced till were much economical when compared to other treatments. Experiment II on “Carbon dynamics of organic residues” was carried out in microplots by studying the litter decomposition pattern for the three type of residues – maize (r1), banana (r2) and pineapple (r3), which were used in Experiment I. The residues were maintained in plots either as surface mulch (m1)or incorporation (m2). Control plots also were maintained without mulching. 6+1 (control) treatments were replicated thrice in factorial randomized block design. At the end of the study after one year time, it was noticed that maize residue decomposed almost completely whereas pineapple residue the least. With progress of decomposition, there was a decline in the percentage residue constituents except for lignin and ash. Higher status of soil organic carbon, soil organic matter and soil enzymes like dehydrogenase, urease and phosphatase were observed in surface mulched pineapple plots. The availability of nitrogen in soil was significantly high for maize residue plots by six months of time but by the time of one year, pineapple residue added plots had significantly higher nitrogen status. The results of the investigation reveals that pineapple residue with high lignin content and hence slow decomposition rates can enrich the organic matter status of soil even one year after it’s application especially when used as surface mulch. Coconut – pineapple cropping systems can be encouraged with surface mulching of residue and reduced till practices so as to enrich SOM and SOC for improved soil quality and to reap better profits.